Contemporary nutrition interventions to optimize performance in middle-distance runners - Stellingwerff, T.; Bovim, I. M.; Whitfield, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Middle-distance runners utilize the full continuum of energy systems throughout training, and given the infinite competition tactical scenarios, this event group is highly complex from a performance intervention point of view. However, this complexity results in numerous potential periodized nutrition interventions to optimize middle-distance training adaptation and competition performance. Middle-distance race intensity is extreme, with 800- to 5,000-m races being at ~95% to 130% of VO2max. Accordingly, elite middle-distance runners have primarily Type IIa/IIx fiber morphology and rely almost exclusively on carbohydrate (primarily muscle glycogen) metabolic pathways for producing adenosine triphosphate. Consequently, the principle nutritional interventions that should be emphasized are those that optimize muscle glycogen contents to support high glycolytic flux (resulting in very high lactate values, of >20 mmol/L in some athletes) with appropriate buffering capabilities, while optimizing power to weight ratios, all in a macro- and microperiodized manner. From youth to elite level, middle-distance athletes have arduous racing schedules (10-25 races/year), coupled with excessive global travel, which can take a physical and emotional toll. Accordingly, proactive and integrated nutrition planning can have a profound recovery effect over a long race season, as well as optimizing recovery during rounds of championship racing. Finally, with evidence-based implementation and an appropriate risk/reward assessment, several ergogenic aids may have an adaptive and/or performanceenhancing effect in the middle-distance athlete. Given that elite middle-distance athletes undertake ~400 to 800 training sessions with 10-25 races/year, there are countless opportunities to implement various periodized acute and chronic nutrition-based interventions to optimize performance.